Stakeholder's Needs Analysis Methodology For Civil Aircraft Projects. Issue 1 (March 2021) - Yuwei, He; Haomin, Li; Xinai, Zhang; Yaming, Shi; Fudong, Chen
Abstract: Aircraft product development process is quite complex, involving many stakeholders. Therefore, aircraft owner manufacturers need to fully capture the needs of stakeholders at the beginning of design, establish analysis methods of stakeholder's needs, and transform "customer voice" into aircraft development requirements, so as to ensure that the aircraft products can meet the needs of stakeholders. This paper introduces stakeholder's needs analysis methods such as quality function deployment (QFD), analytic hierarchy process (AHP), and analytic network process (ANP). This paper establishes a Stakeholder's needs analysis model, which can be used to carry out stakeholder's needs analysis of civil aircraft.